2012
DOI: 10.1111/j.1365-2923.2012.04299.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two methods of teaching reflective ability in Year 3 medical students

Abstract: We found that the provision of critical reflection guidelines improved performance and that feedback on both content and reflective ability also improved performance. Our study demonstrates that teaching learners the characteristics of deeper, more effective reflection and helping them to acquire the skills they need to reflect well improves their reflective ability as measured by performance on reflective exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 38 publications
(47 reference statements)
3
66
0
Order By: Relevance
“…While reflective practice enhances the development of competent, self-directed, lifelong learning, [4][5][6][7][8] mentoring, 9 professional development 7,[10][11][12][13][14][15][16][17][18] critical evaluation, [19][20][21] and problem-solving strategies, [22][23][24] there is limited published literature on the use of reflective practice in pharmacy education or practice. 4,[24][25][26][27] Reflective practices have been used to educate doctors, nurses, physiotherapists, occupational therapists, and other allied health students in higher education, 5,19,23,[28][29][30][31][32][33] to assist in bridging the gap between theory and practice. Thus, it is unclear why pharmacy education has not embraced the use of reflective practice.…”
Section: Introductionmentioning
confidence: 99%
“…While reflective practice enhances the development of competent, self-directed, lifelong learning, [4][5][6][7][8] mentoring, 9 professional development 7,[10][11][12][13][14][15][16][17][18] critical evaluation, [19][20][21] and problem-solving strategies, [22][23][24] there is limited published literature on the use of reflective practice in pharmacy education or practice. 4,[24][25][26][27] Reflective practices have been used to educate doctors, nurses, physiotherapists, occupational therapists, and other allied health students in higher education, 5,19,23,[28][29][30][31][32][33] to assist in bridging the gap between theory and practice. Thus, it is unclear why pharmacy education has not embraced the use of reflective practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability to direct these efforts to areas of greatest need is likely to be highly dependent on informed feedback from the learners' advisors in the form of guided reflection. 13 Therefore, it would be important to explore the concordance of each individual resident's learning goal selection and quality of his or her learning plan with priorities set by the resident's program director and/or advisor. Programmatic interventions could be designed and evaluated to support and assist faculty or peer mentors to help learners self-evaluate and develop realistic and valid goals.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although previous research has found that physicians are poor self-assessors, 10,11 self-assessment can improve with feedback, [12][13][14] and self-assessment has been described as the main influence on appropriate learning goal formation. 15 Because learning goal development is an important step in self-regulated learning, we were interested in exploring how a selfassessment process informed learning goal formation.…”
mentioning
confidence: 97%
“…There is no clear definition or consensus on what reflective practice entails and how it should be fostered and taught. [4][5][6][7] Of concern is that this lack of characterization has not suppressed the tendency to promote reflection despite admissions from medical educators about the difficulty of recommending guidelines for its practice. 7 Moreover, it appears that the terms reflection and reflective practice are generally used interchangeably in medical education.…”
Section: Clarifying Reflection and Reflective Practicementioning
confidence: 97%